2013
DOI: 10.2139/ssrn.2381537
|View full text |Cite
|
Sign up to set email alerts
|

Scrapping Subsidies During the Financial Crisis -- Evidence from the Europe

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The shaded areas indicate the presence of the first car-scrappage program in each country after January 2008. The introduction and ending dates for all programs are taken from Leheyda and Verboven (2013).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The shaded areas indicate the presence of the first car-scrappage program in each country after January 2008. The introduction and ending dates for all programs are taken from Leheyda and Verboven (2013).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Heimeshoff and Mueller () found a significant positive effect of the program on car sales in their analysis of 23 OECD countries. Leheyda and Verboven () demonstrate that the average fuel consumption of newly purchased cars fell by only 0.5 to 1.3 percent. Pfeifer and Klößner () suggest that the German program would actually hurt the environment due to increased CO 2 emissions over the life span of new cars.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Heimeshoff and Mueller () and Leheyda and Verboven () estimate the following equations: log ( s a l e s i t ) = α P R O G i t + X i t β + c i + η t + ε i t , where i represents a country or a country‐model pair, t represents time (often measured in months), sales is new car sales, PROG is a dummy variable indicating that a cash‐for‐clunkers program is in effect, X is a set of other controls, c i is a country‐specific effect and η t is a year‐specific constant. Mian and Sufi () employ a similar strategy but use a cross‐city variation in exposure to the program (i.e.…”
mentioning
confidence: 99%
“…Acemoglu et al (2012) 2 At the time, detailed information information could be found in ACEA(European Automobile Manufacturers' Association)'s website, "Fleet Renewal Schemes in the European Union 2010" and "Fleet Renewal Schemes in the European Union 2009" or IHS Global Insight.3 For a literature review on VSS see e.g Böckers et al (2012). orHeimeshoff and Müller (2013) and the references quoted therein.4 These studies focus in specific programmes as CARS (Cars Allowance Rebate System) in 2009 in the US, the Balladur and Juppé scrappage schemes in 1995-96 in France, the Plan Prever in 1997 in Spain and the Umweltprämie in 2009 in Germany.5 Heimeshoff and Müller (2013) andLeheyda and Verboven (2013) analyze the overall performance of the 2009-2010 programs worldwide and in Europe, respectively. Their results also suggest positive sales with small pull-forward effects in most countries.6 Our analysis restricts to eight countries: Belgium, Germany, Spain, France, Italy, Netherlands, Austria and Portugal.…”
mentioning
confidence: 99%
“…http://www.lavanguardia.com/mobi/noticia/54063606540/El-hundimiento-de-la-venta-de-cochesamenaza-al-sector.html8 Copeland and Kahn (2013) find that the 2009 US program had only a modest and fleeting impact on production, as inventories buffered the movement in sales Leheyda and Verboven (2013). touches slighlty upon the issue of producers, but more based on firm's nationality than country of production ECB Working Paper 2094, August 2017…”
mentioning
confidence: 99%